2002
DOI: 10.1016/s0014-5793(02)03350-1
|View full text |Cite
|
Sign up to set email alerts
|

The novel endoplasmic reticulum (ER)‐targeted protein HAP induces cell apoptosis by the depletion of the ER Ca2+ stores

Abstract: HAP, a novel human apoptosis-inducing protein, was identi¢ed to localize exclusively to the endoplasmic reticulum (ER) in our previous work. In the present work, we reported that ectopic overexpression of HAP proteins caused the rapid and sustained elevation of the intracellular cytosolic Ca 2+ , which originated from the reversible ER Ca 2+ stores release and the extracellular Ca 2+ in£ux. The HeLa cells apoptosis induced by HAP proteins was not prevented by establishing the clamped cytosolic Ca 2+ condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…To clarify the requirement for Ca 2ϩ flux in Gal-9-mediated apoptosis, apoptosis was induced by Gal-9 in the presence or the absence of an extracellular Ca 2ϩ chelator 4 mM EGTA (Dojindo, Kumamoto, Japan) (38), or cells were also preincubated with either intracellular Ca 2ϩ chelator 30 M BAPTA-AM (Dojindo) for 10 min (39) or an inositol trisphosphate (IP 3 ) inhibitor 30 M 2-aminoethoxydiphenyl borate (2-APB; Calbiochem, San Diego, CA) for 10 min (40,41), followed by treatment with 1 M Gal-9.…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…To clarify the requirement for Ca 2ϩ flux in Gal-9-mediated apoptosis, apoptosis was induced by Gal-9 in the presence or the absence of an extracellular Ca 2ϩ chelator 4 mM EGTA (Dojindo, Kumamoto, Japan) (38), or cells were also preincubated with either intracellular Ca 2ϩ chelator 30 M BAPTA-AM (Dojindo) for 10 min (39) or an inositol trisphosphate (IP 3 ) inhibitor 30 M 2-aminoethoxydiphenyl borate (2-APB; Calbiochem, San Diego, CA) for 10 min (40,41), followed by treatment with 1 M Gal-9.…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…A large body of evidence suggests that a variety of agents, including DNA damaging agents, calcium ionophores, and inhibitors of protein glycosylation, can alter the calcium homeostasis and lead to cell death (Nakagawa and Yuan, 2000;Nixon, 2000;McConkey and Nutt, 2001;Nutt et al, 2002). During apoptosis, the changes in the intracellular pool of Ca 2þ and a subsequent increase in cytoplasmic Ca 2þ levels have been demonstrated (Martikainen and Isaacs, 1990;Rao et al, 2001;Qu et al, 2002). In the present study, we observed an increase in Ca þ2 levels in cells exposed to b-lapachone within 10 min by time-lapse confocal microscopy (Fig.…”
Section: Characterization Of the Human Endothelial Cells And Detectiomentioning
confidence: 99%
“…Caspase-12, that is always upregulated during the ER stress, increased 3 h after b-lapachone treatment but downregulated after 6 h administration of b-lapachone. Caspase-12 is localized to the ER and is cleaved into the active form that activates the Ca 2þ -dependent cysteine protease, calpain (Nakagawa and Yuan, 2000;Rao et al, 2001;Qu et al, 2002) Moreover, ER stress can induce conformational changes and oligomerization of Bak and Bax on mitochondrial and ER membranes, leading to loss of ER membrane integrity and Ca 2þ release from the ER, and to apoptosis (Nutt et al, 2002;Zong et al, 2003). To examine the involvement of calpain in the mechanism of blapachone-mediated endothelial cell apoptosis, Western blot analysis was used and showed that calpain activation occurred after 12 h of treatment with b-lapachone and that the intracellular Ca 2þ chelator, BAPTA-AM, or the general calpain inhibitors, ALLM and ALLN, provided significant protection against the effect of b-lapachone (Figs.…”
Section: Characterization Of the Human Endothelial Cells And Detectiomentioning
confidence: 99%
“…ER also functions as a mobilizable calcium store that sequesters excess cytosolic calcium and acts as a reservoir for calcium signaling which maintains intracellular Ca 2þ homeostasis (Sambrook, 1990). A growing body of evidence suggests that changes in intracellular Ca 2þ homeostasis play an important role in the modulation of apoptosis (Pinton et al, 2001;Tagliarino et al, 2001;Qu et al, 2002). Various cell death stimuli including growth factor withdrawal (Jayadev et al, 2000), hormonal stimulation (Wang et al, 1999), and drug treatment (Jayadev et al, 2000) are known to alter the concentration of Ca 2þ in the cytosol and the storage of Ca 2þ in the intracellular organelles, which plays some roles in the cell death pathway.…”
mentioning
confidence: 99%
“…Analysis of protein demonstrated HAP was a reticulon (RTN) family protein RTN3 (Moreira et al, 1999), characterized by two transmembrane domains and a potential C-terminal ER retrieval signal. Our previous study demonstrated that the overexpression of RTN3 caused apoptosis with the depletion of ER Ca 2þ stores and the elevation of cytosolic Ca 2þ (Qu et al, 2002). However, we know very little about the characteristics of the Ca 2þ signals and their functional roles in RTN3-induced apoptotic process, and the proapoptotic mechanism and function of RTN3 remain to be elucidated.…”
mentioning
confidence: 99%